Sistem Rankl/RANK/OPG - nova tarča za zdravila za zdravljenje osteoporoze - Mencej Bradač, Simona (Farmacevtski vestnik, 2008)
Data show that RANKL/RANK/OPG system is an important new target for drugs for osteoporosis treatment. It is one of the local factors that influence bone remodelling or bone resorption. Its primary influence is on the osteoclastogenesis, in which osteoclasts develop, and on mature osteoclast activation. Following RANKL binding to RANK receptor the osteoclast differentiation, activation and fusion are accelerated, their survival is prolonged and the apoptosis is decreased. Bone resorption is increased and followed by bone loss and development of diseases like osteoporosis. On the other hand, OPG binding to RANKL prevents RANKL effects and leads to decreasedbone resorption and increased bone mass. Therapeutic implications of active substances, influencing RANKL/RANK/OPG system, have also been studied and the best results were obtained from the use of OPG-Fc fusion protein and human monoclonal RANKL antibody denosumab. Due to possible risks with OPG-Fc fusion protein application, the use of denosumab is far more promising.
Keywords: drug; osteoporoza; therapy; zdravila; zdravljenje